(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article investergatied philosophical and etnological interpryes "etnoculture" and his please in the sostial-historical prossersies, shape of life, traditions and integration prossersies by people mass.